2019
DOI: 10.1590/abd1806-4841.20198578
|View full text |Cite
|
Sign up to set email alerts
|

Second-to-fourth digit ratio and seborrheic dermatitis in males: a cross-sectional study*

Abstract: Background Seborrheic dermatitis is a common disease characterized by the erythematous plaques with oily-yellow desquamation. Increased sebaceous gland activity by androgenic hormones has played a role in the etiology of the disease. The second-to-fourth digit (2D:4D) ratio is thought to be a marker of prenatal androgen exposure. Objectives To investigate the association between 2D:4D ratios and seborrheic dermatitis in a male population. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 24 publications
0
5
1
1
Order By: Relevance
“…The 2D:4D ratio positively correlates with IL-6; the change in balance in favor of prenatal estrogen can be used for screening low-grade inflammation after birth. 23 Female patients with psoriasis had a lower 2D:4D ratio compared with females in the control group in our study, suggesting that the disruption of the fetal estrogen-testosterone balance against estrogen is a predisposing factor for the development of psoriasis in females; however, the results were not statistically significant. In this study, male patients with psoriasis had a higher 2D:4D ratio for both hands compared with males in the control group.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…The 2D:4D ratio positively correlates with IL-6; the change in balance in favor of prenatal estrogen can be used for screening low-grade inflammation after birth. 23 Female patients with psoriasis had a lower 2D:4D ratio compared with females in the control group in our study, suggesting that the disruption of the fetal estrogen-testosterone balance against estrogen is a predisposing factor for the development of psoriasis in females; however, the results were not statistically significant. In this study, male patients with psoriasis had a higher 2D:4D ratio for both hands compared with males in the control group.…”
Section: Discussioncontrasting
confidence: 70%
“…Estrogen deficiency in females and testosterone deficiency and high estrogen levels in males cause exacerbation of psoriasis. The 2D:4D ratio positively correlates with IL‐6; the change in balance in favor of prenatal estrogen can be used for screening low‐grade inflammation after birth 23 . Female patients with psoriasis had a lower 2D:4D ratio compared with females in the control group in our study, suggesting that the disruption of the fetal estrogen‐testosterone balance against estrogen is a predisposing factor for the development of psoriasis in females; however, the results were not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Triggering factors include stress and cold, dry weather (Gary, 2013;Borda and Wikramanayake, 2015). The prevalence is higher in men than women, potentially due to hormonal influence by androgens (Islamoglu, 2019). However, this may also be a result of differences in grooming practices between genders.…”
Section: Direct Pathogenesis: Malassezia In Seborrheic Dermatitis Andmentioning
confidence: 99%
“…In the current literature, only one study found that the relationship between seborrheic dermatitis and 2D: 4D finger length ratios were evaluated, in the study, only male cases were taken (10). In the study, in male seborrheic dermatitis cases, 2D: 4D finger length ratios in the right hand were significantly lower than the control group (10). In our findings, the rate of lefthand 2D: 4D fingers was found to statistically significantly lower only in patients with male seborrheic dermatitis compared to the control group.…”
Section: Discussionmentioning
confidence: 99%